Polarization or “squeezed middle” in the Great Recession?: A comparative European analysis of the distribution of economic stress - Whelan, C; Nolan, B; Maitre, B (Springer Verlag, 2016)
This paper analyses variation in the impact of the Great Recession on economic stress across income classes for a range of advanced European countries. Our analysis shows Iceland, Ireland and Greece to be quite distinctive in terms of increases in their multidimensional income, material deprivation and economic stress profiles. Between 2008 and 2012 these countries moved from being predictably located within anticipated welfare regimes to becoming clear outliers. For this set of counties, each of which was exposed to different but severe forms of economic shock, trends in income class polarisation versus middle class squeeze were variable. Each exhibited substantial increases in levels of economic stress. However, changes in the pattern of income class differentiation were somewhat different. In Iceland a form of middle class squeeze was observed. For Ireland income class polarization did not exclude middle class squeeze. Greece came closest to fitting the polarization profile. Changes in the distribution of household equivalent income had no effect on stress levels once the impact of material deprivation was taken into account. Changes in levels of material deprivation played a significant role in accounting for changing stress levels but only for the three lowest income classes. These findings bring out the extent to which the impact of the Great Recession on the distribution of economic stress across classes varied even among the hardest-hit countries. They also serve to highlight the advantages of a multidimensional approach that goes beyond reliance on income in seeking to understand the impact of such shocks.